2021
DOI: 10.1101/2021.01.28.21250280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unmet need of essential treatments for critical illness in Malawi

Abstract: BackgroundCritical illness is common throughout the world and has been the focus of a dramatic increase in attention in the COVID-19 pandemic. Severely deranged vital signs can identify critical illness, are simple to check and treatments that aim to correct derangements are established, basic and low-cost. The aim of the study was to estimate the unmet need of essential treatments for severely deranged vital signs in all adults admitted to hospitals in Malawi.MethodsWe conducted a cross-sectional study with f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…We were unable to obtain this data via clinical audit as pulse oximetry coverage was too low and hypoxaemia cannot be accurately determined using clinical signs alone. 9 Alternative approaches to measuring oxygen access to patients are using cross-sectional hypoxaemia and oxygen therapy surveys, 19 crude counts of patients who receive oxygen or relying on HCW recall about oxygen supply stock-outs. 20 These approaches are problematic and provide a poor indication of whether oxygen is actually reaching those who need it.…”
Section: Is Oxygen Therapy Provided To All Patients Who Need It?mentioning
confidence: 99%
“…We were unable to obtain this data via clinical audit as pulse oximetry coverage was too low and hypoxaemia cannot be accurately determined using clinical signs alone. 9 Alternative approaches to measuring oxygen access to patients are using cross-sectional hypoxaemia and oxygen therapy surveys, 19 crude counts of patients who receive oxygen or relying on HCW recall about oxygen supply stock-outs. 20 These approaches are problematic and provide a poor indication of whether oxygen is actually reaching those who need it.…”
Section: Is Oxygen Therapy Provided To All Patients Who Need It?mentioning
confidence: 99%
“…Recent studies from Nigeria and Malawi have shown that without routine pulse oximetry to guide oxygen therapy, only around 20% of hypoxaemic patients receive oxygen – even if adequate oxygen supplies are available. 9 15 Given that pulse oximetry is essential to identifying who requires oxygen and routine pulse oximetry is rare without oxygen supplies, 5 13 pulse oximetry coverage (i.e. the proportion of patients who receive pulse oximetry and have SpO 2 documented) may be a reasonable proxy for patient oxygen access.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to obtain this data via clinical audit as pulse oximetry coverage was too low and hypoxaemia cannot be accurately determined using clinical signs alone. 8 Alternative approaches to measuring oxygen access to patients are using cross-sectional hypoxaemia and oxygen therapy surveys, 15 crude counts of patients who receive oxygen, or relying on HCW recall about oxygen supply stock-outs. 16 These approaches are problematic and provide a poor indication of whether oxygen is actually reaching those who need it.…”
Section: Patient Accessmentioning
confidence: 99%
“…The basic clinical processes specified in EECC have been overlooked in healthcare [11, 13-15, 18, 20, 51, 52] In UK hospitals, half of patients received substandard basic vital organ support prior to intensive care and 31% of preventable deaths were associated with absent clinical monitoring [13,14]. In Malawi, 89% of adult hypoxic patients, and 75% of children dying from pneumonia in hospital did not receive oxygen [17,18]. The usual organisational set-up of health services may be one underlying reason for this.…”
Section: Eecc Complements the Current Healthcare Organisationmentioning
confidence: 99%
“…Unfortunately, this care is frequently a neglected part of healthcare. The basic, life-saving clinical processes may be overlooked in specialised care [12] and in settings of both high [13][14][15] and low resources [16][17][18]. In hospitals all over the world, guidelines, equipment, and routines focusing on the care of critically ill patients, are often missing for adult [19] and paediatric patients [11], in emergency units [20], in wards [21] and in intensive care units [22].…”
Section: Introductionmentioning
confidence: 99%